2009
DOI: 10.1053/j.gastro.2009.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic DNA Polymers Inhibit Hepatitis C Virus Infection by Blocking Viral Entry

Abstract: BACKGROUND & AIMS-Hepatitis C virus (HCV) gains entry into susceptible cells by interacting with cell surface receptor(s). Viral entry is an attractive target for antiviral development because of the highly conserved mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 44 publications
3
72
1
Order By: Relevance
“…binding inhibition. This phenomenon could be extended to the inhibition of virus entry, as it has been recently shown that human cytomegalovirus, hepatitis C virus, and HIV entry are blocked by phosphorothioate-modified ODNs, regardless of CpG motifs (33)(34)(35)(36). One could therefore take advantage of this to design antiviral vaccines that target virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…binding inhibition. This phenomenon could be extended to the inhibition of virus entry, as it has been recently shown that human cytomegalovirus, hepatitis C virus, and HIV entry are blocked by phosphorothioate-modified ODNs, regardless of CpG motifs (33)(34)(35)(36). One could therefore take advantage of this to design antiviral vaccines that target virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous amphipathic interactions may underlie the ability of NAPs to block entry of herpes simplex virus 2 (HSV-2), cytomegalovirus (CMV), and hepatitis C virus (HCV) (16)(17)(18).…”
Section: Uck Hepatitis B Virus (Dhbv) In Its Natural Host the Pekimentioning
confidence: 99%
“…The exact mechanisms of these molecules require further investigations. Other compounds such as serum amyloid A [145,146], p7 ion channel-derived peptide H2-3 [147], amphipathic DNA polymers [148], lactoferrins [149], tellimagrandin I and its derivatives [150], indole derivatives [151], and imidazo [1,2α] [1,8]naphthyridine derivatives [152] were found able to inhibit HCV entry with mechanisms that remain to be clarified.…”
Section: Additional Candidate Entry Inhibitorsmentioning
confidence: 99%